2010
DOI: 10.1080/13674676.2010.510829
|View full text |Cite
|
Sign up to set email alerts
|

Mental well-being in the religious and the non-religious: evidence for a curvilinear relationship

Abstract: Previous studies demonstrating a positive relationship between religiosity and mental health have sampled from a highly religious general population with little differentiation between weak religiosity and non-religiosity. Church members are typically compared with non-religious unaffiliated individuals, thus confounding belief with group effects (e.g. social support). The present study examined mental well-being, utilising the full range of certainty of belief or non-belief in God. In the first study, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
126
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(147 citation statements)
references
References 27 publications
18
126
2
1
Order By: Relevance
“…There is a substantial body of evidence suggesting that R/S is associated with better physical and mental health (Hill & Pargament, 2008), though the relationship is typically quite small (Koenig, 2009). While recent research has demonstrated the presence of a curvilinear relationship between belief and health (i.e., confidently religious and atheist individuals report higher well-being than religiously uncertain and agnostic individuals; see Galen & Kloet, 2011a, for a review), other research contends that atheists tend to experience more psychological problems and are generally less happy than religious people (Altemeyer, 2010;Reed, 1991;Schumaker, 1992;Steinitz, 1980;see Zuckerman, 2009, for a review). While these findings have been attributed to "constructing a moral system from scratch" or "a lack of accountability to God or a wider community" (Hall, Koenig, & Meador, 2008, p. 371), the possible effects of social marginalization (perceived and/or actual) have not yet been considered.…”
Section: Introductionmentioning
confidence: 99%
“…There is a substantial body of evidence suggesting that R/S is associated with better physical and mental health (Hill & Pargament, 2008), though the relationship is typically quite small (Koenig, 2009). While recent research has demonstrated the presence of a curvilinear relationship between belief and health (i.e., confidently religious and atheist individuals report higher well-being than religiously uncertain and agnostic individuals; see Galen & Kloet, 2011a, for a review), other research contends that atheists tend to experience more psychological problems and are generally less happy than religious people (Altemeyer, 2010;Reed, 1991;Schumaker, 1992;Steinitz, 1980;see Zuckerman, 2009, for a review). While these findings have been attributed to "constructing a moral system from scratch" or "a lack of accountability to God or a wider community" (Hall, Koenig, & Meador, 2008, p. 371), the possible effects of social marginalization (perceived and/or actual) have not yet been considered.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are reinforced by Galen and Kloet (2011a) who showed differences in wellbeing between strongly associated atheists and less consistent non-believers. Specifically, people who were certain that God does not exist exhibited greater emotional stability then people who were unsure (Galen & Kloet, 2011a). It appears that certainty in the lack of belief in God may separate atheists from other non-religious people.…”
Section: Individual Differences Within Non-religious Groupsmentioning
confidence: 88%
“…Research studying dogmatism in non-religious individuals have been limited in scope (see Crowson, 2009;Hunsberger & Altemeyer, 2006) and there has been no focus on whether group identity serves as a predictor for dogmatism in non-religious individuals, where social identity strength can vary (Galen & Kloet, 2011a). Rokeach (1960) originally described dogmatism as a 'closed mindedness', which can be prevalent in any sample of people, regardless of religious belief.…”
Section: Social Identity and Dogmatismmentioning
confidence: 99%
“…However, analyses of a subset of the samples analyzed in the present study indicated that doubt struggles predict higher life satisfaction and lower levels of depression after controlling for other types of R/S struggles (with theists and atheists pooled as one sample; Exline et al 2014). Some research has supported the idea that certainty in one's worldview-whether a religious or non-religious worldview-predicts better mental health (Galen and Kloet 2011). Given the nuanced conclusions in this area, the association between doubt struggles and well-being among atheists needs to be examined to develop a better understanding of this relationship.…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 89%